Source-to-sink history of detrital garnet from coastal dune sands in SW Mexico - Lizeth Carlos Delgado; Juan J. Kasper-Zubillaga; Raymundo G. Martínez-Serrano; Mayumy Amparo Cabrera Ramírez; Elsa Arellano-Torres; José Luis Sánchez Zavala (Geosystems and Geoenvironment)
A morphological and geochemical study of detrital garnet was conducted to assess its utility in understanding sedimentary processes in coastal dune sands caused by in a weathering-limited erosion regime along the southwestern coast of Mexico. Multiple analytical techniques helped to elucidate the garnet's provenance, shape modification and surface alteration during its source-to-sink sedimentary dispersal. A Wavelength Dispersive Spectrometry (WDS) in an Electron Microprobe Analyzer (EMPA) (n = 89) revealed the dominance of almandine as the main mineral type related to the ortho-paragneiss source rocks from the Oaxacan Complex with a lesser contribution from the Xolapa Complex, outcropping in northwestern of the coastal dune sands. Scanning Electron Microscopy (SEM) helped to assess the compactness and convexity of shape descriptors by contouring the outline of detrital garnet (n = 200) and to identify the microtextures of the mineral's surface. A Raman Spectroscopy (n = 17) was employed to determine the presence of hydroxide or oxyhydroxide coatings to quantify the chemical weathering degree caused by steady and shallow burial conditions. Results show that the detrital garnet mainly underwent aeolian abrasion followed by fluvial subaqueous and marine controls. The former was supported by the quantification of moderate to high compactness and convexity values and the SEM observation of aeolian mechanical microtextures like bulbous edges, adhering particles and abrasion fatigue compared to the subaqueous microtextures as large conchoidal fractures (>50 µm). Finally, we found that low to moderate chemical dissolution control modified the detrital garnet's surficial texture, evidenced by chemical microtextures like solution pits, etch pits, etch features, imbricate wedge marks and mound features. Hence, detrital garnet dissolution was dominated by its chemical composition, the nonstoichiometric character of the dissolution rate and its crystallographic forms.